An Analysis of US State Regulated Weed Lists: A Discordance between Biology and Policy. (26th August 2020) - Lakoba, Vasiliy T; Brooks, Rachel K; Haak, David C; Barney, Jacob N
Abstract: Weedy and invasive plants threaten our food supply, native biodiversity, and the structure and function of ecosystems. The number and impact of these damaging plants are expected to continue to grow with ongoing global change. Some of the most common policy tools to help mitigate this threat are regulatory weed lists, which limit the importation and movement of listed plant species, but there has never been a comprehensive analysis of plants regulated in the United States. We analyzed US state regulatory lists (e.g., noxious, invasive, prohibited) to evaluate their composition, patterns of listing, congruities with weed distributions, and limitations. In total, 46 states maintain regulatory weed lists that include 3210 total listings of 1249 unique species; 48% of them are introduced, 40% are native, and 12% are not yet found in the United States. Overall, the listed species are not a good reflection of the weeds in each state, and listing appears largely reactive, regulating species after they become widespread. We highlight patterns and incongruities among lists and discuss their implications, especially the large number of regulated species native to the United States.